Pertanggungjawaban Hukum Terhadap Pelaku Promotor Perjudian Online - Faisyal Akbar; Maya Shafira; Emilia Susanti; Deni Achmad; Dona Raisa Monica (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The promotion of online gambling through social media such as Instagram and WhatsApp is increasingly attracting public interest, even though it violates the law in accordance with Article 27 Paragraph (2) of Law Number 19 of 2016. Case at the Tanjung Karang District Court (Number 892/Pid.Sus/2023/PN .TJK) revealed that online gambling promotion is a criminal offense with the threat of prison sentences and fines. What is the criminal liability of perpetrators who promote online gambling products and what is the basis for the judge's considerations in imposing criminal penalties on perpetrators who promote online gambling products? Data analysis uses qualitative data analysis. The judge's decision is in accordance with applicable law, taking into account legal, sociological and philosophical aspects. In this case the judge placed more emphasis on the sociological and philosophical aspects. Hakim used Mackenzie's theory, emphasizing balance, artistry, intuition, and a scientific approach. Criminal liability must be strictly legally necessary to protect society from the negative impacts of online gambling. The criminal liability contained in decision number 892/Pid.Sus/2023/PN.TJK regarding online gambling promotion involves several defendants. This decision emphasizes the importance of law enforcement in maintaining justice and public security, and shows the appropriate application of the law to punish the promotion of illegal gambling.